Efficient bioconversion of l-glutamate to γ-aminobutyric acid by Lactobacillus brevis resting cells. (1st May 2017) - Shi, Xiufeng; Chang, Chuanyou; Ma, Shenxi; Cheng, Yibing; Zhang, Jun; Gao, Qiang
Abstract: This work investigated the efficient bioconversion process of l -glutamate to GABA by Lactobacillus brevis TCCC 13007 resting cells. The optimal bioconversion system was composed of 50 g/L 48 h cultivated wet resting cells, 0.1 mM pyridoxal phosphate in glutamate-containing 0.6 M citrate buffer (pH 4.5) and performed at 45 °C and 180 rpm. By 10 h bioconversion at the ratio of 80 g/L l -glutamic acid to 240 g/L monosodium glutamate, the final titer of GABA reached 201.18 g/L at the molar bioconversion ratio of 99.4 %. This process presents a potential for industrial and commercial applications and also offers a promising feasibility of continuous GABA production coupled with fermentation. Besides, the built kinetics model revealed that the optimum operating conditions were 45 °C and pH 4.5, and the bioconversion kinetics at low ranges of substrate concentration (0 <  S  < 80 g/L) was assumed to follow the classical Michaelis–Menten equation.